Perfil epidemiológico dos idosos que foram a óbito no Hospital Universitário de Santa Maria - Penna, Márcia Aparecida (2019)
Population aging is now considered a worldwide phenomenon and the most significant trend of the 21st century. The change in the demographic profile is associated, among other factors, with the improvement of public health, with technological advances and the reduction of the fertility rate, associated to the drop in infant mortality and, the expansion of the treatment of common diseases in the elderly. The causes of death represent an important pattern of the living and health conditions of a given population, therefore, it is believed that knowing the characteristics of elderly patients who died, enables healthcare professionals to plan care for these patients as well as the organization of the service in relation to the managerial aspects of human and material resources, contributing for the team to prepare to attend these patients considering the trend of the profile of the user population of the service. Therefore, the present study aimed to describe socioeconomic and causal indicators that may be related to the mortality of the elderly in the HUSM between 2015 and 2016. This is an observational study of a historical cohort of patients over 60 years of age hospitalized and died at the Hospital Universitário de Santa Maria. The data were collected in the period from January to March of 2018, by means of own instrument, previously tested. The ethical aspects of Resolution no. 466/12 of the National Health Council of the Ministry of Health. The research was approved by the Research Ethics Committee of UFSM, according to opinion No. 2,465,290, under the number of CAAE 81628518.2.0000.5346. The accomplishment of this study made it possible to know the profile of the deaths in the elderly in the Hospital Universitário de Santa Maria, and the results obtained are presented in three articles format. The first deals with a reflection on the aging population and the public policies of attention to the elderly; the second, an integrative review on the profile of mortality in the Brazilian elderly, and the third refers to an observational study of a historical cohort and descriptive nature of the profile of the deaths in the elderly in the Hospital Universitário de Santa Maria.